Using a Cooperative Educational Game to Promote Pro-Environmental Engagement in Future Teachers - Mercedes Vázquez-Vílchez; Dalia Garrido-Rosales; Beatriz Pérez-Fernández; Alicia Fernández-Oliveras (MDPI AG, 2021)
This paper explores the value of cooperative games in enhancing knowledge and generating pro-environmental engagement in students. For this, an educational board game related to global change was developed, validated, and subsequently evaluated using future primary school teachers. The board game was validated and evaluated in two phases. Phase I (validation phase): students pursuing a Master's Degree in Secondary Education evaluated different aspects of the game, providing feedback that improved the game design and playing rules. Phase II (implementation-evaluation phase): the game was implemented using students of the Primary Education Degree, whose learning performance and engagement was assessed through a qualitative survey. These participants were considered potential users of the board game. The users' experience was explored using a theoretical framework for pro-environmental engagement through playing the game. The findings demonstrate that the cooperative game proposed fomented a feeling of personal responsibility for the environment in the users. It also fostered cognitive, emotional, and behavioural engagement in the players. The results agree with the attributes present in the framework of engagement with respect to climate-change-related issues using gaming. Game-based learning can be used as a tool for enhancing global change knowledge and promoting pro-environmental engagement while bolstering Education for Sustainability (EfS) capacity in future primary-school teachers.